Relationship of Self Concept with Self-Acceptance of Drug User Prisoners - Tiara Indah Dewanti; Yulidar Ibrahim (Universitas Negeri Padang, 2019)
An individual who can accept himself is an individual who has an awareness of the characteristics that are inside him, and he is able and willing to live with these characteristics, and individuals are not trapped in anger, blame others and pity themselves for the limitations they have. Self-acceptance is important for prisoners of drug users, useful to facilitate the recovery of individual drug users to a state of physical, psychological, and social functioning. One's self-acceptance is influenced by a stable self-concept. This study aims to empirically examine the relationship of self-concept with self-acceptance in prisoners of drug cases in the Padang II Class Correctional Institution. This research is a descriptive correlational research with quantitative methods. Sampling in this study used a purposive sampling technique with a total sample of 60 drug users. The research instruments used were self-concept questionnaire and self-acceptance questionnaire. The results of the study revealed that (1) the self-concept of drug users in Padang Class IIA Correctional Institution was mostly in the high category (2) self-acceptance of drug users in Padang Class IIA Correctional Institutions were mostly in the good category (3) significant between self-concept and self-acceptance of drug users in Padang II Class Correctional Institution.